Comparison for oral health-related quality of life in fibromyalgia subgroups according to fibromyalgia impact questionnaire: A preliminary study (Annals of Medical Research, 2021)
Aim: This study aimed to compare the relationship between the severity of fibromyalgia and oral health-related quality of life in participant subgroups according to the fibromyalgia impact questionnaire.. Materials and Methods: Forty female participants aged 46.18±8.91 years old who were diagnosed with fibromyalgia were included in the study. Demographic data, education status, smoking, systemic anamnesis, employment status was recorded. Decayed, missing and filled teeth index values, periodontal situation and removable prosthesis conditions were evaluated. Participants were asked to fill three self-reported questionnaires: the fibromyalgia impact questionnaire, oral health impact profile-14 and general oral health assessment ındex scores. Fibromyalgia subgroups were classified as FM-Type I and FM-Type II according to the Souza et al classification. The primary outcome of which relationship between subcategorize of oral health related quality of life indexes and fibromyalgia impact questionnaire values were evaluated with Spearman correlation analysis. Results: The total value of oral health impact profile-14 was found to be 12.25±9.17 in the FM-Type I group and 19.74±10.48 in the FM-Type II group. There was a statistically significant relationship between fibromyalgia subgroups and oral health impact profile-14 psychological impacts (p=0.031) and total values (p=0.023). The values of total fibromyalgia impact questionnaire scores were obtained on a wide scale between 34.08 and 93.34, and the mean value was measured as 67.06 ± 16.06. The fibromyalgia impact questionnaire median cut-off score was detected as 66.42 according to ROC analysis.Conclusion: The higher negative oral health related quality of life values were observed in participants more severely affected by fibromyalgia. In addition to medical and psychiatric treatment of fibromyalgia participants, evaluation of dental conditions may be suggested.
Keywords: Fibromyalgia; oral health; quality of life; surveys and questionnaires